Thermal Testing of Corundum Ceramics: Pulsed Heating and Optimized Data Processing Algorithms; Russian Journal of Nondestructive Testing; Vol. 60, iss. 9 - Chernykh S. E. Sergey; Vavilov V. P. Vladimir Platonovich; Kostin V. N. Valeriy; Komolikov Yu. I. Yuriy; Kladov D. Dmitry (2024, 2024)
A review of defect types in the production of corundum ceramic tiles and conventional methods for testing the integrity of products made from this material has been conducted. The integrity of tiles containing artificial defects was studied using the active thermal testing method with pulsed optical heating. A two-sided thermal testing setup was employed with software processing of the initial thermograms using Parker’s method. It was established that the best results for detecting internal defects in 10 mm thick ceramic tiles during thermal stimulation with xenon lamps are achieved by the two-sided thermal testing method with the construction of thermal diffusivity maps